Changes in The Organisational Framework of Cooperation Within Urban Areas in Hungary - Somlyódyné Pfeil, Edit (Discussion Papers, 2012)
The objective of the present study is to detect, while urban networks are accorded an increasingly important role in EU Cohesion policy, with what regulatory and support environment Hungarian cities and urban areas enter the competition of European cities. On the basis of our analysis our conclusion is that even though Hungary outlined its urban policy in the form of creating a polycentric and cooperative urban network, the system of instruments accompanying the planning documents is weak and incompatible with the defined objectives. Consequently, we cannot speak about a comprehensive urban policy, merely of its certain components. To underly this fact, the author presents the public legal regulation of the system of self-government and spatial development which hardly extends to questions of city-suburban cooperation, and criticizes the system of multi-purpose small-regional associations from the viewpoint of the spatial organisational role of cities. The author investigates the institutional frameworks of cooperation in the agglomeration of Budapest and other three Hungarian agglomerations, and tries to define the position of urban development in the system. The study ends with the definition of alternative and lacking regulatory frameworks of urban policy.